Diaphragmatic Paralysis - S. Zulkifli; H. E. Monintja; M. Sutan Assin (Paediatrica Indonesiana, 1974)
To the authors knowledge not one publication on diaphragmatic paralysis in the newborn is available in the Indonesian literature. This paper communication is to report some cases of diaphragmatic paralysis with Erb's palsy in the newborn and in early infancy detected in Jakarta.